Effect of water extracts of some medicinal plants seed on germination percentage Trifolium alexandreum L. - Abdullhussein, Taif M.; Al- Hasnawy, Riyadh A.; AL-Selawy, Razaq L .; Kashkool, Haider R.; alkanany, Ahmad A.; Muhamed, Mustafa (Journal of Kerbala for Agricultural Sciences, 2016)
A factorial experiment was conducted at the laboratories of the College Agriculture – Kerbala University during 2015. The aim was to effect of water extracts of some medicinal plants seed enhancement on germination percentage.The design of lab. Experiment was CRD with three replicates. Each experiment consisted of one factors: water extracts (T1= Distilled water),(T2 =Fenugreek),(T3= Sweet Fennel),(T4 =Black cumin),(T5= Cumin). Results of Lab. Water extracts that T5 treatments significantly increased the germination percentage (98.33%), plumule length(4.21cm) and dry weight plumule (22.70mg). while the T5,T4 treatments was superior in giving the higher average of germination speed (5.03 and 4.75 seed / day) ,force seedling (23.28and 21.88) , radical length(1.61cm and 1.47cm) and dry weight radical (8.13mg and 7.85mg) respectively. compared with the T1 treatment (control) which gave the lowest values of percentage germination, germination speed, force seedling, length of radical, length of plumule , dry weight radical, and dry weight plumule (92.33 , 4.61 seed / day ,20.81, 1.22cm,5.60cm,3.45mg and 21.40mg) respectively. Water extracts that T2, T3 appear inhibition all most parameters studies.